Pengaruh Collateralizable Assets, Free Cash Flow, Ownership Structure, dan Corporate Governance Terhadap Kebijakan Dividen pada Perusahaan LQ45 yang Terdaftar di Bursa Efek Indonesia Tahun 2019 – 2023 - Ramadhani, Noviana; Hidayati, Cholis (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
The research objective is to analyze the effect of collateralizable assets, free cash flow, ownership structure, and corporate governance on dividend decision-making policies in LQ45 companies on the IDX for the 2019-2023 period. Quantitative methods are used in this study with secondary data sources. The population in this study were 45 LQ45 companies listed on the Indonesia Stock Exchange in 2019-2023 with a sample of 16 companies selected through purposive sampling method with certain criteria. Some of the independent variables in this study include collateralizable assets proxied by COLLAS and Asset Guarantee indicators, free cash flow proxied by FCF and FCFE indicators, ownership structure proxied by KM, KI, and KA indicators, and corporate governance proxied by DKI, DD, and Audit Committee indicators. Data analysis uses analysis techniques from Structural Equation Modeling (SEM) through Partial Least Squares (PLS) software. The findings in this study indicate that only collateralizable assets have a significant effect on dividend policy. Free cash flow, ownership structure, and corporate governance variables do not show a significant effect on dividend policy.